Office and school furniture manufacture from paper waste (2015)
The aim of this paper is to present the development of a material and a machine that enable the manufacturing of furniture from waste paper from offices and schools. The method uses the TRIZ methodology. Criteria were established to evaluate the material to be developed, and different settings were experimented to create a suitable material for making furniture. Furthermore, a machine was constructed to speed up the manufacturing process. The manufactured furniture is only made by using paper, biodegradable adhesive, and either textile waste or water based paint for its finishing. Its manufacturing process is easy transfer and at a very low cost. A year after having manufactured the first piece of furniture, it remains in good condition, despite having been exposed to conditions for which it was not designed.